2014
DOI: 10.7314/apjcp.2014.15.19.8405
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Temozolomide Treatment for Patients with Glioma

Abstract: Background: This analysis was conducted to evaluate the efficacy and safety of temozolomide based chemotherapy in treating patients with glioma. Methods: Clinical studies evaluating the efficacy and safety of temozolomide based regimens for patients with glioma were identified using a predefined search strategy. Pooled response rates (RRs) were calculated. Results: In temozolomide based regimens, 5 clinical studies including 152 patients with advanced glioma were considered eligible for inclusion. Four clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Although some studies have suggested that after lumbar decompression, physical therapy intervention does not significantly affect clinical outcomes, as measured by patient-reported outcomes and surgical outcomes [24,25], numerous approaches aimed at improving nursing quality, such as brain storming, world café, and management by objectives, have been created since the World Health Organization has defined quality nursing as a patient-oriented, fair, convenient, effective, highly efficient, safe and acceptable model of nursing [26]. Studies have shown that personalized nursing that involves the application of a scientific, systemic and standardized nursing program and plan is effective for postoperative rehabilitation [27,28]. In addition, intimate and comprehensive nursing also contributes to communication and relationships between patients and nurses, which is beneficial for improving the quality of nursing and the outcome of surgery [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested that after lumbar decompression, physical therapy intervention does not significantly affect clinical outcomes, as measured by patient-reported outcomes and surgical outcomes [24,25], numerous approaches aimed at improving nursing quality, such as brain storming, world café, and management by objectives, have been created since the World Health Organization has defined quality nursing as a patient-oriented, fair, convenient, effective, highly efficient, safe and acceptable model of nursing [26]. Studies have shown that personalized nursing that involves the application of a scientific, systemic and standardized nursing program and plan is effective for postoperative rehabilitation [27,28]. In addition, intimate and comprehensive nursing also contributes to communication and relationships between patients and nurses, which is beneficial for improving the quality of nursing and the outcome of surgery [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection, radiotherapy, chemotherapy, and other comprehensive treatment modalities were implemented, the majority of patients exhibited an unfavorable prognosis. Consequently, the exploration of novel biomarkers for early detection has emerged as a pivotal endeavor to enhance the diagnosis and management of glioma [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…It does realize joint nursing, and it optimizes communication and promotes the relationship between patients and nurses so that the quality of nursing is improved[ 15 , 16 ]. In comprehensive nursing, effective personalized nursing can be provided to patients by using a scientific, systemic and standardized nursing program and nursing plan[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%